Integration of Human Organisational Technological Factors and Information Quality Metrics for Assessing Hospital Information System Performance - Rumambi, Frendy Rocky; Prasetya, Didik Dwi; Patmanthara, Syaad (Emerging Information Science and Technology, 2025)
Digital transformation in health care necessitates HISs that can efficiently integrate people, organisations, and technology to deliver best performance in service delivery. This paper proposes a HIS performance evaluation model solution based on humanorganisation– technology fit (HOT-Fit) and information quality metrics (IQM) concept to evaluate system success technically. This model modifies the HOT-Fit model by incorporating an information quality metrics dimension with four constructs: accuracy, completeness, timeliness, and relevance. Research Methodology: The study follows quantitative approach and the survey questionnaires were filled by 150 active SIRS users from which the data was analysed using SEM. The findings suggest that the technology quality and information quality constructs significantly influence both user satisfaction and system use. Information quality is established as a mediating variable in the relationship between technological factors and user satisfaction. From a practical perspective, this integrated model has implications for understanding that achieving SIRS success depends not only on how well humans, organisations, and technology fit together but on the quality of the data and information produced. This research is a step towards the advancement of data metric based information system evaluation specifically in the domain of Health Infor matics, and also serves as a conceptual framework for enhancing HIS governance in Indonesia.